Oral health care in the elderly population in Malaysia - a review - John, J.; Mani, S.A.; Azizah, Y. (Malaysian Medical Association, 2004)
One of the undeniable facts about living is that everyday we are getting older. By 2050, it is projected that one out of every five Malaysians will be 60 or older. The economic challenge of this demographic change will affect development and the financial implications of sustaining well being of this group are formidable and complex. This population group has extensive oral disease, medical problems that complicate their oral care, and unique dental treatment challenges. The authors discuss the problem of oral healthcare among the aged, its impediments and propose some approaches for improvement to better serve the needs of this group of vulnerable members of our nation.